Pengaruh Umur Bibit Batang Bawah dan Teknik Penyambungan terhadap Pertumbuhan Bibit Jambu Biji (Psidium guajava L.) - I WAYAN ADI WIRAWAN; I PUTU DHARMA; ANAK AGUNG MADE ASTININGSIH (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2018)
Influence of Seedling Age of Rootstock and Technique of Grafting to Growth of Guava Seedlings (Psidium guajava L.) The age of rootstock seedlings and grafting techniques can influence the success of plant propagation by grafting. The alternative that can be done is to use some age of rootstock seedlings and the technique of grafting in the propagation of guava plants. The experiment was conducted in farmer's garden located in Banjar Tiyingan, Pelaga Village, Petang Dist. Badung, Bali. The research was started from May 29, 2017 - August 11, 2017. The research used factorial Randomized Block Design (RBD).The first factor was the age of seedlings of guava rootstock, with the age of 3, 4 and 5 month seedlings and the second factor was the V grafting technique and the Cip grafting technique. The result of the research showed that the interaction between the treatment of seed aged and the grafting technique had significant effect on the variable of plant age 75 days after grafted but on the other variable has not significant effect. Age of real seeds can increase the percentage of live grafting, the number of buds at seedling aged 60 days after grafting, the long of buds at aged 45 days after grafting,the diameter of buds at aged 60 and 75 days after grafting. Age of seeds 5 months provide the real growth better than 3 months and 4 months. The real grafting technique can increase the number of buds at seedling aged 30days after grafting, the long of buds at aged 30 days after grafting, totally leaves of the plants at aged 45 and 75 days after grafting, buds’ diameter in each observations, leaf area on eachplantataged 45 days after grafting. The real V grafting technique provide the growth of guava seeds better than the Cip grafting technique.